Respiratory symptoms: a significant factor to be considered in dengue infection - Murugesan, Rajamani; Thiruvengadam, Kannan; Roy, Avijit; Pulikkottil, Sunish; Paluru, Vijayachari (The Journal of Infection in Developing Countries, 2026)
Introduction: Dengue is a major arboviral infection. Clinical manifestations range widely from mild, non-specific febrile syndromes to serious, life-threatening conditions. Dengue cases have increased globally over the last ten years. Dengue patients show gastrointestinal and respiratory symptoms. The aim of this study was to identify the associated demographic risk factors, and evaluate the significance of respiratory symptoms for early diagnosis. Methodology: Blood samples were collected from dengue-suspected patients reported to various health centers in South Andaman, from January 2018 to December 2022, and were processed by antigen/antibody assay. The odds of factors for being dengue positive among dengue suspects were analyzed using the Chi-square test, logistic regression models, and random forest analysis. Results: Blood samples were collected from 14,783 (99.6%) of the 14,836 dengue suspects. Dengue infection was confirmed in 1,354 (9.2%) suspects. A significantly higher prevalence of infection was observed in the age group 16 to 30 years. Resident males of urban areas had higher dengue positives. Fever was a significant clinical manifestation of dengue infection. Rhinorrhea and other respiratory symptoms showed a significant association (p < 0.05) with dengue infection. Conclusions: Respiratory discomfort was found to have a significant association with individuals suspected of dengue. Dengue positivity rate per 1000 population was high among these individuals. This study determined the key signs that can be considered significant to suspect dengue, including respiratory ailments. This will help the healthcare professionals to identify dengue cases at an early stage, to initiate fluid-based treatment.